2012
DOI: 10.1186/1745-6215-13-9
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of consumers in studies run by the Medical Research Council Clinical Trials Unit: Results of a survey

Abstract: BackgroundWe aimed to establish levels of consumer involvement in randomised controlled trials (RCTs), meta-analyses and other studies carried out by the UK Medical Research Council (MRC) Clinical Trials Unit across the range of research programs, predominantly in cancer and HIV.MethodsStaff responsible for studies that were included in a Unit Progress Report (MRC CTU, April 2009) were asked to complete a semi-structured questionnaire survey regarding consumer involvement. This was defined as active involvemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
64
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(67 citation statements)
references
References 12 publications
2
64
0
1
Order By: Relevance
“…70,71 In particular, PPI is seen as being key to the development of plain English summaries as a requirement in many grant applications. 24,62 There are also claims that PPI improves the overall design in trials, 72 particularly by ensuring the design is acceptable for potential participants. 73 Contributing to the design of interventions is reported as being an important aspect of PPI; examples include stroke research interventions 74 and advising on the timing of interventions within Parkinson's disease research.…”
Section: Patient and Public Involvement: The Methodological Argumentmentioning
confidence: 99%
See 2 more Smart Citations
“…70,71 In particular, PPI is seen as being key to the development of plain English summaries as a requirement in many grant applications. 24,62 There are also claims that PPI improves the overall design in trials, 72 particularly by ensuring the design is acceptable for potential participants. 73 Contributing to the design of interventions is reported as being an important aspect of PPI; examples include stroke research interventions 74 and advising on the timing of interventions within Parkinson's disease research.…”
Section: Patient and Public Involvement: The Methodological Argumentmentioning
confidence: 99%
“…[88][89][90] Dissemination of research findings is also reported as gaining from PPI networks to increase access to peers 81 and relevant sections of the community, 15 and making information more broadly readable. 31,72 There are fewer published claims for PPI as playing a significant role in implementing findings, but, in a US public health research programme, Krieger et al 86 report PPI-related implementation of changes by increasing their cultural relevance. Several researchers have identified that PPI has helped them address ethical dilemmas, 17,71,78,85,91 for example ethically appropriate ways of contacting women with recently diagnosed breast cancer and the use of routine patient data.…”
Section: Patient and Public Involvement: The Methodological Argumentmentioning
confidence: 99%
See 1 more Smart Citation
“…Some HIV research had involved community engagement [10], and the Population Council had established a microbicide stakeholder advisory committee. In addition, in 1998 the United Kingdom (UK) Medical Research Council recommended consumer involvement in the conduct of clinical trials [11] as a means to more relevant research, more effective translation of research and more open communications [12]. Still, the use of committees composed of lay people (whether stakeholders or stakeholder subgroups such as consumers or community members) who had an interest in or were affected by research was in its early stages.…”
Section: Fhi 360 Involvement With Quinacrinementioning
confidence: 99%
“…For å sikre at forskningen som utføres er relevant, for eksempel at utfallene som blir målt er pasientrelevante, kan pasienter delta som partnere i forskningsprosjekter (38,52,53). I kliniske forsøk kan pasienter vaere involvert i hele forsøksprosessen, både i planlegging, rekruttering og gjennomføring, og i arbeidet med å implementere og formidle resultatene fra forskningen (52,54). Det finnes eksempler på at pasienter har deltatt som intervjuere i forskningsprosjekter (55).…”
Section: Områder For Medvirkningunclassified